Long‐term cochlear implantation outcomes in patients following head injury - Lubner, Rory J. (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVE: In cases of a severe to profound sensorineural hearing loss following head injury, the cochlear implant (CI) is the primary option for auditory rehabilitation. Few studies, however, have investigated long‐term CI outcomes in patients following head trauma, including those without temporal bone fracture (TBF). Herein, the aim of this study is to examine CI outcomes following cases of head injury with and without TBF. METHODS: Audiometric outcomes of patients who received a CI due to a head injury resulting in severe to profound hearing loss at two tertiary care hospitals were analyzed. Patients were divided into those who received a CI in a fractured temporal bone (group A, n = 11 patients corresponding to 15 ears) and those who received a CI in a non‐fractured temporal bone (group B, n = 8 patients corresponding to nine ears). Primary outcomes included duration of deafness prior to CI and postoperative consonant‐nucleus‐constant whole word (CNC) scores. RESULTS: Nineteen patients (84% male), corresponding to 24 CIs, were identified. Fifteen CI were performed on ears with TBF (group A), and nine CI were performed on ears without TBF (group B). No patients had an enlarged vestibular aqueduct (EVA). The mean duration of deafness was 5.7 and 11.3 years in group A and group B, respectively. The mean duration of CI follow‐up (CI experience) was 6.5 years in group A and 2.1 years in group B. The overall mean postoperative CNC score for all subjects was 68.6% (±21.2%, n = 19 with CNC testing). There was no difference in CNC score between group A and group B (69.8% and 66% respectively, P = .639). CONCLUSION: The study is among the largest series examining long‐term outcomes of CI after head injury. CI is an effective method for auditory rehabilitation in patients after head injury. LEVEL OF EVIDENCE: IV.